MQTTProvider: A flexible MQTT traffic generator for the performance evaluation of complex Smart Cities scenarios - Sales, Michel; Santos, Mateus P.; Rego, Paulo A. L. (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2024)
In smart cities, designing intelligent spaces incorporating Internet of Things (IoT) applications is crucial for enhancing urban efficiency and quality of life. However, developing these applications requires real data at scale, which can be complex and non-trivial to obtain. A real traffic generator aids in modeling unpredictable traffic, validating IoT configurations, evaluating network performance, and improving cybersecurity and privacy solutions. In this sense, we introduce the MQTTProvider, an adaptable IoT traffic generator for simulating various smart spaces and supporting time-driven, event-driven, mobile, actuators, and complex devices. It was designed to integrate with IoT Middleware, such as FIWARE. Experiments indicate that MQTTProvider can be used to assess the scalability of IoT platforms.